2006
DOI: 10.1002/j.2161-0045.2006.tb00153.x
|View full text |Cite
|
Sign up to set email alerts
|

Vocational Skills and Outcomes Among Native American Adolescents: A Test of the Integrative Contextual Model of Career Development

Abstract: This study tested hypotheses of the Integrative Contextual Model of Career Development (R. T. Lapan, 2004a) by investigating the multivariate effects of 6 interrelated career development skills (career exploration, personenvironment fit, goal setting, social/prosocial/work readiness, self-regulated learning, and the utilization of social support) on 6 intermediate vocational outcomes (academic achievement, self-efficacy expectations, positive selfattributions, vocational interests, vocational identity, and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 25 publications
2
27
0
1
Order By: Relevance
“…Evidence supported H4 and H5. The association between self-efficacy expectations and career exploration is consistent with the previous literature (e.g., Lent et al, 2016;Turner et al, 2006). Further research could test the joint role of career self-efficacy expectations and career exploration in children's approach or avoidance of activities (Lent et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Evidence supported H4 and H5. The association between self-efficacy expectations and career exploration is consistent with the previous literature (e.g., Lent et al, 2016;Turner et al, 2006). Further research could test the joint role of career self-efficacy expectations and career exploration in children's approach or avoidance of activities (Lent et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
“…These opportunities advance cognitive representations about one's prospective capability to successfully perform similar activities in the future (Lent & Brown, 2013). Research has supported these assertions by suggesting positive associations between career self-efficacy and career exploration (e.g., Lent, Ezeofor, Morrison, Penn, & Ireland, 2016;Turner et al, 2006). Longitudinal evidence from childhood through adolescence has also indicated positive associations among career selfefficacy expectations, academic achievement, and the likelihood to continue or drop out of school (Caprara et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…This implies that career education intervention not only helps students find their careers and overcome obstacles but also helps them learn career development skills and have success in school. Some studies (Arbona, 2000;Turner & Lapan, 2013;Turner et al, 2006) have identified the role of career development skills based on the ICM as a mediator of school success. Holland's (1997) model emphasizes the importance of congruence between career guidance and student interest.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that parents' beliefs about gender differences in children's abilities are transmitted to and internalized by their children (Eccles Parsons, Adler, & Kaczala, 1982;Frome & Eccles, 1998) and that there are ethnic differences in the messages that children internalize from their parents (Whiston & Keller, 2004). Opportunities for skill development vary considerably and may contribute to differences in career-related self-efficacies (Lent et al, 1994;Turner et al, 2004). Despite different socialization, the same career development and occupational choice processes seem to occur for men and women as well as European Americans and minorities (Lent et al, 2005).…”
Section: Socialization and Career Choicesmentioning
confidence: 99%